Enhancing Operational Efficiency in FMCG Customer Care: Design and Implementation of a High-Performance Web-Based Knowledge Management System Using Next.js with Hybrid Rendering Architecture - Alghifari Rasyid Zola; meredita susanty (IJNMT (International Journal of New Media Technology), 2026)
In the highly competitive Fast-Moving Consumer Goods (FMCG) sector, the speed and accuracy of customer support are critical differentiators. This study addresses a significant operational bottleneck at PT Paragon Technology and Innovation, where reliance on fragmented, static documentation led to high information retrieval latency and service inconsistencies. To mitigate these issues, we designed and developed an integrated Knowledge Management System (KMS) serving as a Single Source of Truth (SSOT). Engineered using an Agile methodology, the system utilizes a modern Full-stack architecture based on the Next.js framework. It employs a hybrid rendering strategy, leveraging Server-Side Rendering (SSR) to optimize load performance and Client-Side Rendering (CSR) for interactive interfaces. The backend integrates a PostgreSQL database managed via Prisma ORM to ensure data integrity. Key features include a unified global search engine and a transparent audit trail mechanism for governance. Post-implementation evaluation indicates that the system significantly reduces agent search time and enhances data validity through real-time tracking. These findings demonstrate the efficacy of modern web architectures in transforming legacy workflows into a responsive, data-driven customer service ecosystem.